A Rare Anomaly of the Long Head of the Biceps Brachii Muscle - S Kumar; R Baidya; P Baral (Journal of Gandaki Medical College, 2018)
Introduction: Biceps brachii is a muscle of arm which brings about supination when fore-arm is flexed and flexion of elbow joint. Proximally it is attached with two heads: long and short heads.